PENGARUH RELIGIOSITAS DAN RASA PERCAYA TERHADAP TOLERANSI BERAGAMA DI SUMATERA SELATAN - Heryadi, Ferry (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
Indonesia, as a religious and pluralistic country, faces major challenges in maintaining interfaith tolerance. This study aims to understand the influence of religiosity and trust on attitudes of religious tolerance among students of Islamic religious colleges in South Sumatra. Using a quantitative approach and survey method involving 387 respondents, this study examines the influence of religiosity, trust, and demographic factors (such as age, education, and occupation) on attitudes of religious tolerance through multiple linear regression analysis. The results of the study indicate that religiosity and trust have a significant positive effect on religious tolerance. The higher the level of religiosity and trust between individuals, the greater the tendency of respondents to be tolerant. On the other hand, demographic factors such as age, gender, occupation, and parental expenditure level do not have a significant effect on tolerance. The regression model also indicates that religiosity and trust, although their contribution is not large, are important factors in understanding attitudes of religious tolerance in society. These findings encourage policy recommendations, such as strengthening religious moderation programs, optimizing the role of FKUB, and increasing trust between individuals through social programs, training of religious figures, tolerance campaigns in the media, and interfaith activities in schools. In conclusion, the integration of inclusive religious values ??and increasing mutual trust are important steps to strengthen religious tolerance in Indonesia, with the hope of strengthening the identity of a harmonious nation in diversity.